A framework for evaluating the performance of thai tourism industry supply chain management - Palang D. (2017)
© IEOM Society International. In Thailand, tourism is a major industry for economic and social development of the country. Tourism generates revenue worth hundreds of thousands of Baht into the country each year. Thai tourism industry is growing faster than ever with US$26,680 million generated in revenue in 2013. Consequently, Thai tourism industry was rated fifth in Asia in terms of revenue by the Pacific Asia Travel Association. Tourism industry is the service industry that affects a variety of economic activities such as hotels, airlines, car rent, trains, restaurant, commodity, furniture, shopping malls, entertainment complex, spa and wellness, convenient stores, souvenir shops etc. These service activities are supplied by different companies, organization and agents. Unlike other industries, tourism industry is unique. Its only product that customers can have is satisfaction and experience. That very tourist spot can be sold forever. Tourism supply chain(TSC)management becomes effective in improving business performance and competitive benefit. In spite of this, there is limited amount of research on TSC performance measurement when compared to researches for manufacturing industries. This paper develops a framework Tourism Industry Supply Chain performance evaluation model. The emphasis is on the impact of performance indicators on each tier of the inbound of Thai tourism industry supply chain from customers perspective and proposes a model of the performance measurement of to TSC that initiates improving business performance. The framework employs the nine dimensions of service performance which are order process management, supplier relationship management, service performance management, capacity and resources management, customer relationship management, demand management, information and technology management, tour finance supply chain and hierarchical structure supply for tourism and a methodology base on fuzzy Multi-Criteria Decision Making(MCDM) to search suitable performance measurement for each supply chain member and applies Structural Equation Modeling (SEM) to evaluate the impact of performance indicator on each tier. © IEOM Society International.